Trends and climate variability of cold fronts and rainfall in the metropolitan region of Sao Paulo - Segura, Caroline Santos (2024)
Cold fronts play a crucial role in the precipitation regime in southeastern Brazil, especially in the metropolitan region of São Paulo (RMSP). Understanding the trends and variabilities of these systems and the associated rainfall is essential for assessing local climate impacts. This study aims to analyze the characteristics of cold fronts, precipitation, and their extremes, contributing to an improved understanding of climate trends in the region. It also examines the ability of the ERA-20C reanalysis to capture the observed climatology of cold fronts. Between 1960 and 2010, an average of 39.6 cold fronts per year were observed at the meteorological station located in the RMSP. The ERA-20C showed results very close to those obtained from observations. Precipitation extremes were identified using the 95th percentile of daily precipitation (in mm) for each month, considering only days with precipitation above 0 mm. In the period 1960-2010, this criterion resulted in 486 extreme precipitation events, of which 290 may be related to the passage of cold fronts in the RMSP. Trends for time series of precipitation, cold front frequency, and extreme precipitation were analyzed using the Mann-Kendall test. Only the time series of accumulated annual precipitation showed a significant linear growth rate.